Nutrition: Transforming food systems to achieve healthy diets for all - Ruel, Marie T.; Brouwer, Inge D. (International Food Policy Research Institute, 2021)
Pre-pandemic, 3 billion people could not afford a healthy diet; that number could rise by 267.6 million due to the pandemic. Food system transformation must support healthy diets and tackle all forms of malnutrition. KEY MESSAGES - Evidence from phone surveys in low- and middle-income countries shows widespread job and income losses and rapid rises in food insecurity due to government measures to contain the pandemic; poorer households, women, and other vulnerable groups are most affected. - Across the globe, the quality of diets deteriorated due to disruptions in supply of fresh, healthy foods, drops in demand for these foods due to unaffordability and perishability, and increased consumption of cheaper sources of calories including starchy staples and ultra-processed foods. - Deteriorations in diet quality could have devastating consequences for the health and nutrition of vulnerable women and children and could increase all forms of malnutrition in the short term and cause lifelong, irreversible development, health, and nutrition damage, reversing decades of progress made so far. - Food system transformation must support healthy diets and by doing so, serve as double duty actions that simultaneously tackle all forms of malnutrition.